The Legal Review of the Budgeting Mechanism for Village Funds for Sustainable Development Programs - Arjunanda, Ahmad Dicky; Lestari, Marselli Septia; Nuzulurrizki, Ahmad; Sivana, Aina Firda (MultiTech Publisher, 2024)
This research aims to analyze in depth the mechanism of village fund budgeting in the context of sustainable development programs. The research method used in this study is normative juridical, the mechanism is in achieving sustainable village development goals and identifying the obstacles and challenges faced. As a result, some of the results of development projects became stalled and had an impact on the preparation of subsequent planning. The results showed that the utilization and supervision of information technology had a positive impact on the accountability of village resource management. Thus, it is expected that the management of village funds can be more effective and equitable development can occur.